Forms of Narration through the Web-Based Documentary: the Europa Dreaming Case - Burgio, Valeria; Moretti, Matteo (E|C, 2020)
This essay analyses the design process for a visual communication project, the final product of which is a website. Conceived within the sphere of Visual Journalism, the goal of the website is to gather and compare various ways of understanding the "European dream" by putting together a montage of different media and languages (photography, video, infographics, reusing images from the archives). It thus responds through a kaleidoscope of points of view to the hyper-simplified story of the presumed migrant invasion of Europe and its portrayal as an emergency by the sensationalist press. The choice of a medium such as the web, using the same means as the news we wish to deconstruct, makes it possible to collate different voices, different places, different historical periods, to bring critical scope and depth to the fleeting flash of today's news. The choices of structure, language and genre lend themselves to a plural type of project that coalesces heterogeneous elements around a core of arguments. The authors’ point of view attempts a difficult mediation between ex-post analysis and the involvement in the design process, using semiotic tools to motivate the aesthetic, linguistic and structural choices made earlier during the design process.